BUS PATAS SEBAGAI ALTERNATIF PEMECAHAN MASALAH UNTUK OPTIMALISASI PRESTASI AKADEMIK DAN NON AKADEMIK PESERTA DIDIK DI SMA NEGERI 1 GANTUNG - Sabarudin Sabarudin (Khazanah Pendidikan, 2016)
“BUS PATAS” focus on the daily activities of the school were directed to the achievement of academic and non academic all students by allocating education resources (teachers, staff, equipment, supplies, materials, and funds) in order to achieve the vision, mission and objectives of the school agreed. Development of school achievement both in academic and non-academic via the “BUS PATAS”, conducted by three (3) main principles, namely: (a) raising Culture Superior School, (b) make up the school community who have Active Participation and responsibilities in school activities, and (c) build a shared commitment to success in academic and non-academic. The results of the implementation of the “BUS PATAS” includes: (a) the school culture superior to being a necessity (classroom becomes more conducive, the creation of a school environment that is safe, clean, green, orderly, religious, and familial, and the growing culture of quality in the neighborhood school), (b) start embedding the active participation and responsibility of the school community (the implementation of development educators who are competent and dedicated and implemented the management of education personnel effectively), (c) the establishment of a shared commitment to success (growth aspirations for high achievement growth and a willingness to change).